2019
DOI: 10.1016/j.eucr.2019.100992
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic-directed therapy using PSMA-PET/CT at PSA relapse

Abstract: The side effects of androgen deprivation therapy (ADT) as general treatment against prostate cancer are known to impair quality of life. However, the optimal onset of ADT at PSA relapse is unknown, especially in patients with normal testosterone. In our case a limited PSMA avid lymph node was detected on PET/CT. Our case highlights the importance of metastasis-directed therapy balancing general versus tailored treatment in the decision making in the era of advanced molecular imaging. By using PSMA-PET/CT and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The study found a longer ADT-free survival with MDT than surveillance alone. Only very few studies have been published on the results of MDT based on results from PSMA PET/CT [ 140 ]. Mazzola et al compared the impact of 18 F-choline and 68 Ga-PSMA PET/CT-guided MDT with stereotactic body radiotherapy (SBRT) in patients with castration-sensitive oligorecurrent PCa [ 141 ].…”
Section: Clinical Applicationmentioning
confidence: 99%
“…The study found a longer ADT-free survival with MDT than surveillance alone. Only very few studies have been published on the results of MDT based on results from PSMA PET/CT [ 140 ]. Mazzola et al compared the impact of 18 F-choline and 68 Ga-PSMA PET/CT-guided MDT with stereotactic body radiotherapy (SBRT) in patients with castration-sensitive oligorecurrent PCa [ 141 ].…”
Section: Clinical Applicationmentioning
confidence: 99%